2017
DOI: 10.11648/j.jhrm.20170502.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Learning Organization Culture on Organizational Performance Among Logistics Firms in Mombasa County

Abstract: This research was set to establish the effect of learning organization culture on the performance of Logistics firms in Mombasa County. The specific objectives of the study were to establish whether Individual level learning, team level learning and organization level learning affect organizational performance. A descriptive design was adopted and stratified random sampling was used to select the subjects to be included in the study. A total of 171 employees were sampled from a population of 300 employees. Que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…Furthermore, the revelation made regarding continuous learning and performance of the staff is in line with the findings of Hussein et al (2016) and Behjanna and Sharifi (2015). This study also confirmed the studies of Aktar et al (2011), Wetherington and Daniels (2013), Harris and Samreen (2015) and Mrisha et al (2017) relative to the relationship inquiry and dialogue has with employee performance. It is also in line with the assertions of Marsick and Watkins (2003) and Yang and Chen (2005), bordering collaboration and team learning.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the revelation made regarding continuous learning and performance of the staff is in line with the findings of Hussein et al (2016) and Behjanna and Sharifi (2015). This study also confirmed the studies of Aktar et al (2011), Wetherington and Daniels (2013), Harris and Samreen (2015) and Mrisha et al (2017) relative to the relationship inquiry and dialogue has with employee performance. It is also in line with the assertions of Marsick and Watkins (2003) and Yang and Chen (2005), bordering collaboration and team learning.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Wetherington and Daniels (2013), on the relationship between learning organisation dimensions and employee performance in the non-profit sector, revealed that there exists a positive relationship between inquiry and dialogue and job performance. Mrisha et al (2017) also indicated a positive and strong relationship between inquiry and dialogue and staff performance.…”
Section: People Aspect Of Learning Organisation and Employee Performancementioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, the other five dimensions (embedded systems, teamwork, leadership, continuous learning, and empowerment) had an insignificant relationship with the organizational performance. This is in line with the study reported in [62], which examined the effect of learning organization culture on organizational performance using the DLOQ to measure learning organization in Kenya. The results showed that the dimensions of collaboration and team learning and continuous learning had a positive but weak relationship with organizational performance, whereas employee empowerment had a positive but average relationship with the performance.…”
Section: Learning Organization and Organizational Performancesupporting
confidence: 88%